Characterization of UBO-QIC as a Gαq inhibitor in platelets. (17th November 2015) - Inamdar, Vaishali; Patel, Akruti; Manne, Bhanu Kanth; Dangelmaier, Carol; Kunapuli, Satya P
Abstract: Gαq plays an important role in platelet activation by agonists such as thrombin, adenosine diphosphate (ADP) and thromboxane. The significance of Gαq signaling in platelets was established using YM254890, a Gαq/11 -specific inhibitor and Gαq knockout murine platelets. However, YM-254890 is no longer available for investigators and there is a need to characterize other Gαq inhibitors. The aim of this study is to characterize the specificity of a compound, {L-threonine, (3R)-N-acetyl-3-hydroxy-L-leucyl-(aR)-a-hydroxybenzenepropanoyl-2, 3-idehydro-N-methylalanyl-L-alanyl-N-methyl-L-alanyl-(3R)-3-[[(2S, 3R)-3-hydroxy-4-methyl-1-oxo-2-[(1-oxopropyl)amino]pentyl]oxy]-L-leucyl-N, O-dimethyl-, (7→1)-lactone (9CI)} (UBO-QIC), as a Gαq inhibitor in platelets. Human platelets treated with UBO-QIC showed a concentration-dependent inhibition of platelet aggregation and secretion by protease-activated receptors (PAR) agonists, U46619 and ADP. UBO-QIC also abolished Gαq pathway signaling events such as calcium mobilization and pleckstrin phosphorylation. UBO-QIC had no nonspecific effects on the Gα12/13 pathway since platelet shape change was intact in Gαq knockout murine platelets stimulated with PAR agonists in the presence of the inhibitor. In addition, UBO-QIC-treated platelets did not affect collagen-related peptide-induced platelet activation suggesting that this inhibitor had no non-specific effects on the GPVI pathway. Furthermore, Akt phosphorylation downstream of the Gαi and Gαz pathways, and vasodilator-stimulated phosphoprotein phosphorylation downstream of the Gαs pathway were not inhibited in UBO-QIC-treated platelets. UBO-QIC is a specific inhibitor for Gαq, which can be a useful tool for investigating Gαq -coupled receptor signaling pathways in platelets.